The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10433-010-0141-9
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to prevent disability in frail community-dwelling older persons: an overview

Abstract: This narrative review was conducted to provide an overview of the variety of interventions aimed at disability prevention in community-dwelling frail older persons and to summarize promising elements. The search strategy and selection process found 48 papers that met the inclusion criteria. The 49 interventions described in these 48 papers were categorized into 'comprehensive geriatric assessment', 'physical exercise', 'nutrition', 'technology', and 'other interventions'. There is a large diversity within and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 76 publications
1
56
0
2
Order By: Relevance
“…Theses advancements in 'agefriendly' environments at home and neighborhoods have contributed to declines in disability (Daniels et al 2010). Freedman et al (2006) found that from 1992 to 2001, a large portion of the decline in numbers of older adults receiving help for ADL limitations was related to greater usage of assistive technology.…”
Section: (E)nvironmental Factorsmentioning
confidence: 99%
“…Theses advancements in 'agefriendly' environments at home and neighborhoods have contributed to declines in disability (Daniels et al 2010). Freedman et al (2006) found that from 1992 to 2001, a large portion of the decline in numbers of older adults receiving help for ADL limitations was related to greater usage of assistive technology.…”
Section: (E)nvironmental Factorsmentioning
confidence: 99%
“…Providing ATDs is one of many interventions occupational therapists use to rehabilitate older individuals and has the promise to be a cost-effective and constructive part of the solution to future health care challenges (3,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Providing ATDs is one of the many interventions used in the rehabilitation of older individuals and is promising as a cost-effective and constructive method for solving future health care challenges [3][4][5][6][7]. Therefore, the provision of ATDs to individuals in need is publicly funded in Norway, and the municipalities are responsible for every aspect of the ATD delivery process [8].…”
Section: Introductionmentioning
confidence: 99%